Effects of antibiotic replacement with garlic powder and probiotic on performance, carcass characteristics, oxidative enzymes and intestinal morphology of broiler chickens - Rastad, Abdolhadi (Acta Scientiarum. Animal Sciences, 2020)
An experiment was conducted to evaluate the effects of probiotic and garlic powder instead of antibiotic on performance, carcass characteristics, oxidative enzymes and intestinal morphology of broiler chickens. A total of 200 one-day-old male broiler chicks were used in a completely randomized design. The experimental groups were including control group (without any additives) or CG, antibiotic group or AG, garlic powder group or GG, probiotic group or PG and garlic powder plus probiotic group or GPG. The broilers were weighted at the end of days 10, 24 and 42 to evaluate the body performance. At the end of experiment, four broilers randomly selected from each replicate to blood sampling and carcass traits measurement (2 chickens for each one). The use of GG significantly decreased feed intake than AG (p < 0.05) which approved in GPG when probiotic added to GG (p < 0.05). All groups, exception GG showed less feed intake than CG between days 0 to 42 of experiment (p < 0.05). GPG shows significant differences than CG between days 21 to 42 and 0 to 42 and also than GG between days 0 to 42. The use of GG and GPG significantly increased liver enzyme activities (p < 0.05). AG, PG and GPG showed a higher height and width villi than CG. So simultaneous use of probiotic and garlic powder can be a suitable alternative to antibiotics to normal performance and liver function